Comparison of an Open versus List-Based Dietary Recall Method to Assess Unhealthy Feeding Practices among Infants and Young Children - Katelyn Yuen-Esco; Guy-Marino Hinnouho; Elaine L Ferguson; Ngik Rem; Hou Kroeun; Chea Mary; Alissa M Pries (Current Developments in Nutrition)
Background: Collecting accurate dietary data is critical for assessing infant and young child feeding practices, identifying populations at risk, and using evidence to inform policy. In 2021, World Health Organization/United Nations Children’s Fund released new indicators of unhealthy food and beverage consumption and recommended that survey administrators use either an open or list-based method. Objectives: This study compared infants’ and young children’ unhealthy food consumption estimated using an open 24-h recall (24HR) compared with list-based 24HR among young children living in peri-urban Cambodia and explored the effect of social desirability bias on respondents’ responses. Methods: We conducted a secondary analysis of unhealthy food consumption estimated in a longitudinal cohort study implemented from June 2021 through January 2022 in the rural/peri-urban district of Khsach Kandal, Kandal Province, Cambodia (567 children aged 10–13.9 mo at baseline). Each month, for 5 mo, data were collected via an open 24HR. At the 6th month, half of the children were randomly assigned to also receive a list-based 24HR to collect data on unhealthy food consumption. Results: The prevalence of sweet beverage and unhealthy food consumption and zero fruit and vegetable consumption among young children was high. We observed that the percentage of children consuming sweet foods was significantly higher when estimated using the list-based compared with an open 24HR method (61.6% compared with 43.8%; P = 0.012). An association between social desirability bias and reported consumption of salty/fried foods was also observed across both groups; however, this relationship was more pronounced among caregivers who received the list-based 24HR than the open 24HR (P = 0.004). Conclusions: Researchers must carefully consider the method used for 24HR because this may have implications for respondents’ recall and memory. As more evidence is collected on the rising consumption of unhealthy food and beverages among young children, researchers should take into consideration the effects of caregiver’s susceptibility to social desirability bias when analyzing these consumption patterns.